(untitled) (Colombia Medica, 2019)
Introduction: High blood pressure (HBP) is the main cardiovascular risk factor, it is more prevalent in the older adult population, and the prevalence can vary between ethnic groups. Objective: To estimate the prevalence of HBP, knowledge, treatment and control in population aged ≥60 years, resident in Colombia, according to their ethnic condition. Methods: Population sample selected by multistage sampling. Ethnicity was defined based on skin color. HBP was defined as systolic blood pressure ≥140, and/or diastolic blood pressure ≥90 mm Hg, and/or the participants’ self-report. Controlled HBP at a blood pressure value <140/90, knowledge and treatment were identified by self-report. Results: 23,694 adults aged ≥ 60 years were included, of which 54.5%, 34.5% and 10.9% were respectively identified as having light, medium or dark skin color; 54.5% were women, and 78.1% resided in urban areas. The standardized prevalence of HBP, by age, was 57.7% (95% CI: 55.2 - 60.2); 51.4% (95% CI: 47.3-55. 5), in men; and 62.9% (60.964.9), in women. The standardized prevalence for light, medium and dark skin in men was 53.2% (95% CI: 48.7-57.7), 49.6% (44.5-54.7), and 49.4% (95% CI: 41.0-57.8) respectively; and in women was 62.5% (95% CI: 60.5-64 , 5), 61.7% (95% CI: 57.865.6), and 69.9% (95% CI: 63.6-76.2) respectively. 98% of the population received treatment, and 93.9% were aware of HBP diagnosis. 42.5% of men and 55.5% of women with HBP were under control. Only 21.8% performed regular physical activity. Conclusion: Half of the adult population aged over 60 years suffers from HBP; the prevalence is higher in women particularly in dark-skinned women. It is necessary to develop policies to increase physical activity in the elderly.